STRUKTUR PEMBIAYAAN DAN PENGARUHNYA TERHADAP PROFITABILITAS BANK MUAMALAT INDONESIA DAN BANK SYARIAH MANDIRI - Amalia, Nur; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the financing structure and its influence to the profitability of Bank Muamalat Indonesia and Bank Syariah Mandiri (in 2009-2013 periods). The method uses descriptive quantitative in order to obtain description how large the financing structure and its influence to the profitability of Bank Muamalat Indonesia and Bank Syariah Mandiri. The data collection technique uses secondary data in which the data has been retrieved from the quarterly financial statement which has been published by every syariah bank which has been selected as sample through the website of each bank. The result of research based on the model feasibility (goodness of fit) shows that the mudharabah, musyarakah, murabahah, istishna, and ijarah financing have influence to the profitability. The result of significance (t test) shows that the mudharabah, musyarakah, murabahah, istishna financing have influence to the profitability. Meanwhile, the ijarah financing does not have any influence to the profitability of Muamalat Bank Indonesia and Mandiri Syariah Bank.Keywords: Financing of Profit Sharing, Purchasing, Rent, and Profitability.